Suitability and Carrying Capacity of Mangrove Ecotourism in Ronela Beach, North Seram District - Merlin Latutiene; Henderina Lelloltery; Andri Tuhumury (Universitas Lambung Mangkurat, 2024)
This research was carried out at Ronela Beach for one month from October 16 to November 16. This study aims to determine the suitability of Ronela Beach Tourism for the Development of Ronela Beach Ecotourism and to analyze the carrying capacity of the Ronela Beach area for Coastal Ecotourism Activities. The method used in this research is survey method with descriptive analysis. To describe in a systematic, factual and accurate manner regarding the suitability and carrying capacity of the Ronela Beach Area for the Development of Coastal Ecotourism in Rumah Olat Hamlet. Data collection techniques used by researchers in this study are interview and observation techniques. The results showed that the suitability and carrying capacity of the Ronela Beach area has a good value to be used as a tourist spot.